MicroRNA expression after ionizing radiation in human endothelial cells - Wagner-Ecker, Mechthild; Schwager, Christian; Wirkner, Ute; Abdollahi, Amir; Huber, Peter E. (Radiation oncology, 2010)
Endothelial cells (EC) in tumor and normal tissue constitute critical radiotherapy targets. MicroRNAs have emerged as master switchers of the cellular transcriptome. Here, we seek to investigate the role of miRNAs in primary human dermal microvascular endothelial cells (HDMEC) after ionizing radiation.
Gesehen am 28.09.2023